Stress, Inflammation and the Irritable Bowel Syndrome - Stephen M Collins; Giovanni Barbara; Bruce Vallance (Canadian Journal of Gastroenterology)
Studies in animals have shown that inflammation of the mucosa of the gastrointestinal tract is accompanied by changes in enteric nerve and smooth muscle function, and in gut motility and sensation. In some instances, these changes persist long after resolution of the mucosal inflammation. Some of these observations have been made in human studies of irritable bowel syndrome (IBS) in patients after an enteric infection or in patients in remission from ulcerative colitis. Stress has also been implicated as a modulator of gastrointestinal inflammation in both animal and human studies. In animals, stress causes a reactivation of previous enteric inflammation and induces the attendant physiological changes. Prior stress also enhances the response to subsequent inflammatory stimuli. In humans, postinfectious IBS tends to occur in patients with psychological profiles similar to those observed in IBS patients and in whom there is a higher incidence of stressful life events just before exposure to the infection. Taken together, these observations link stress and inflammation as a putative pathogenetic mechanism in at least a subset of IBS patients.